Interactions in multiagent systems - Hao, Jianye; Leung, Ho-Fung (Singapore World Scientific, 2019)
This compendium covers several important topics related to multiagent systems, from learning and game theoretic analysis, to automated negotiation and human-agent interaction. Each chapter is written by experienced researchers working on a specific topic in mutliagent system interactions, and covers the state-of-the-art research results related to that topic. The book will be a good reference material for researchers and graduate students working in the area of artificial intelligence/machine learning, and an inspirational read for those in social science, behavioural economics and psychology
Includes bibliographical references and index.
Keywords: Công nghệ thông tin; Trí tuệ nhân tạo